A LEXICAL COHESION ANALYSIS USED IN JOKO WIDODO’S SPEECH “PELUNCURAN INDONESIA EMAS 2045” - Maftuha, Rofiah Ulil; Tjahyadi, Indra; Sutrisno, Adi; Wafa, Hosnol (Program Studi Bahasa Inggris, Universitas Panca Marga, 2024)
This study analyzes the types of lexical cohesion in Joko Widodo’s speech. The research has two main objectives: first, to describe the types of lexical cohesion in Joko Widodo’s speech “Peluncuran Indonesia Emas 2045”. The second, is to describe the functions of lexical cohesion in the same speech. The method used in this research is descriptive qualitative. This method is employed to describe the analysis and findings, which focus on analyzing types of lexical cohesion such as repetition, synonymy, superordinate, general words, and collocation. The data classification and analysis are conducted based on the theory of lexical cohesion proposed by Halliday and Hasan (1976), who classify lexical cohesion into two main groups: reiteration and collocation. The result of the analysis shows that 63 data contained repetition (87,5%), 3 data contained synonymy (4,2%), 2 data contained superordinate (2,8%), 4 data contained collocation (5,6%), and no general words were found in this data. After analyzing the results, repetition was identified as the most dominant type of lexical cohesion, accounting for 87.5% of the instances. However, one type of lexical cohesion, namely general words, was not found in the speech text.